Kiat Menangkal Bahaya Hoax Dari Internet Terhadap Anak-Anak - Ni Made Sulastri; Dewi Rayani; Fitri Astutik (Abdi Masyarakat, 2019)
Community service is aimed at increasing the knowledge and abilities of guardians of students and families in preventing the dangers of hoaxes from the internet to children. This is based on several observations that find indications of most parents or families in the current era of human life and activities of parents, teenagers and even children. Internet becomes one of the interests because all can be obtained with unlimited distance, the internet is always present in everyday life, even children seem to have been sedated with the internet. If we look at activities on the internet, especially on social media, it is not uncommon to find hoak information, the dangers of hoak information if it cannot be prevented or prevented it will be detrimental and can damage human morale. Parents' routines and activities are sometimes an obstacle in dealing with the dangers of hoak in children. Feeling that the impact of hoak information is very detrimental, so it is necessary to take care to prevent the dangers of hoak from the internet on children